(untitled) (Journal of actual problems of jurisprudence, 2019)
It is characteristic that in the advanced countries of the world, despite the high degree of social harmony in the socio-economic development, the political elite and the trade unions avoided apply the term "social partnership", preferring more neutral definitions of the type "social dialogue"and" bilateral consultations". And in our country, despite the economic crisis and social instability, reformers persistently repeat about the success of social partnerships, implying by them: progress in the payment of pensions and wages in budgetary sphere. In other words, what in the West is considered an elementary order, we have it is elevated to the rank of social partnership.